The Influence of Multiliteracy Learning of Local Bima Fiction Texts Based on Multimodal Approach to Improve Students' High Order Thinking Skills - Muhamad Fadli, Bagus; Haris, Abdul; Suharti, Suharti; Faidin, Faidin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
In the digital era, literacy transcends conventional reading and writing, encompassing the ability to understand, analyse, and produce meaning through various media. This research examines the influence of multiliteracy learning based on local Bima fiction texts with a multimodal approach to improve students' Higher Order Thinking Skills (HOTS) through experimental research with quantitative design involving 60 students from MA Darul Hikmah, Bima Regency, divided into experimental group (30 students) and control group (30 students). The learning implementation was conducted for four months using HOTS test instruments and student perception questionnaires, showing significant improvement results in the experimental group with average scores increasing from 74.27 (pre-test) to 82.40 (post-test) or an increase of 8.13 points, while the control group only increased by 3.90 points with significant differences based on statistical tests (t = 8.98, p < 0.0001). Multimodal learning successfully developed students' analytical, evaluation, and creation abilities through various activities such as creating digital infographics and interactive multimedia presentations, with questionnaire data showing very positive responses with an average score of 52.07 out of maximum 60 (86.8%), proving that the integration of multiliteracy, multimodality, and local Bima wisdom is effective in improving students' HOTS and creating more interactive and meaningful learning.